Cost Analysis for Robotic and Open Gastrectomy - Yuki Hirata, MD, PhD; Heather G. Lyu, MD, MBI; Ahad M. Azimuddin, MBA; Pamela Lu, MD; Jeeva Ajith, MBA; Jason A. Schmeisser; Elizabeth P. Ninan, MBA; Kyung Hyun Lee, PhD; Brian D. Badgwell, MD, MS; Paul Mansfield, MD; Naruhiko Ikoma, MD, MS (Annals of Surgery Open)
Objective:. To determine the magnitude of the perioperative costs associated with robotic gastrectomy (RG). Background:. A robotic surgery platform has a high implementation cost and requires maintenance costs; however, whether the overall cost of RG, including all perioperative costs, is higher than conventional open gastrectomy (OG) remains unknown. Methods:. Patients who underwent a major gastrectomy during February 2018 through December 2021 were retrospectively identified. We calculated the perioperative costs of RG and OG and compared them overall as well as in different phases, including intraoperative costs and 30-day postsurgery inpatient and outpatient costs. We investigated factors potentially associated with high cost and estimated the likelihood of RG to reduce overall cost under a Bayesian framework. All cost data were converted to ratios to the average cost of all operations performed at our center in year FY2021. Results:. We identified 119 patients who underwent gastrectomy. The incidence of postoperative complications (Clavien-Dindo >IIIa; RG, 10% vs OG, 13%) did not significantly differ between approaches. The median length of stay was 3 days shorter for RG versus OG (4 vs 7 days, P < 0.001). Intraoperative cost ratios were significantly higher for RG (RG, 2.6 vs OG, 1.7; P < 0.001). However, postoperative hospitalization cost ratios were significantly lower for RG (RG, 2.8 vs OG, 3.9; P < 0.001). Total perioperative cost ratios were similar between groups (RG, 6.1 vs OG, 6.4; P = 0.534). The multiple Bayesian generalized linear analysis showed RG had 76.5% posterior probability of overall perioperative cost reduction (adjusted risk ratio of 0.95; 95% credible interval, 0.85–1.07). Conclusions:. Despite increased intraoperative costs, total perioperative costs in the RG group were similar to those in the OG group because of reduced postoperative hospitalization costs.